ANALISA DAMPAK CAR FREE NIGHT TERHADAP KINERJA JARINGAN JALAN DI KAWASAN ENGGAL BANDAR LAMPUNG - Marina, Bernaditha C (UNIVERSITAS LAMPUNG, 2014)
The purpose of this study is to stimulate the network trip assignment as the result of car free night by applying management and traffic engineering as the solution. The purpose is also to calculate the car free night impact over the road network level of service at Enggal Region Bandar Lam - pung, considered from the traffic flow and Degree of Saturation (V/C Ratio) value. From this re- search and analysis, found that car free night didn’t provide the significant impact to traffic per- formance at Enggal Region, this is shown by the calculation of all road network level of service in the study area which are all of the V/C Ratio values below 0,75. This calculation means the han - dling scenarios of management and traffic engineering become unnecessary. Whereas for 20% validation between traffic performance comparison during manual calculation (MKJI) and simu- lation (Tranplan) at Enggal Region, the result shows only performance of Jl. Majapahit had 240,40% difference in traffic flow. This is caused by the differences in perception between two condition which are intangible.